Educating for Cosmopolitanism: Lessons from Cognitive Science and Literature - Bracher, Mark.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Drawing on developments in cognitive science, Bracher formulates pedagogical strategies for teaching literature in ways that develop students' cognitive capabilities for cosmopolitanism, the pursuit of global equality and justice. Several staple classroom texts, such as Things Fall Apart, provide detailed examples for teaching practices.
Keywords: Science; Science; Science, general